Sendai virus utilizes specific sialyloligosaccharides as host cell receptor determinants. - Markwell, M A (1980)
Purified sialyltransferases (CMP-N-acetyl-neuraminate:D-galactosyl-glycoprotein N-acetylneuraminyl-transferase, EC 2.4.99.1) in conjunction with neuraminidase (acylneuraminyl hydrolase, EC 3.2.1.18) were used to produce cell surface sialyloligosaccharides of defined sequence to investigate their role in paramyxovirus infection of host cells. Infection of Madin-Darby bovine kidney cells by Sendai virus was monitored by hemagglutination titer of the virus produced and by changes in morphological characteristics. By either criterion, treatment of the cells with Vibrio cholerae neuraminidase to remove cell surface sialic acids rendered them resistant to infection by Sendai virus. Endogenous replacement of receptors by the cell occurred slowly but supported maximal levels of infection within 6 hr. In contrast, sialylation during a 20-min incubation with CMP-sialic acid and beta-galactoside alpha 2,3-sialytransferase restored full susceptibility to infection. This enzyme elaborates the NeuAc alpha 2,3Gal beta 1,3GalNAc (NeuAc, N-acetylneuraminic acid) sequence on glycoproteins and glycolipids. No restoration of infectivity was observed when neuraminidase-treated cells were sialylated by using beta-galactoside alpha 2,6-sialytransferase, which elaborates the NeuAc-alpha 2,6Gal beta 1,4GlcNAc sequence. These results suggest that sialyloligosaccharide receptor determinants of defined sequence are required for Sendai virus infection of host cells.